(untitled) (Research, Society and Development, 2023)
Aim: Search for evidence about the assistance of digital technology in the planning and execution of direct restorations. Materials and Methods: An integrative literature review was developed based on the PRISMA model and based on the guiding question: “Are there advantages in using digital technology to create direct restorations?” The exploratory search was carried out on the Pubmed and VHL portals using the descriptors in English MeSH: Dentistry, Direct restoration, 3D, Printing, Digital, composite resin and restorations, with the time limit between the years 2013 to 2023 regarding the time of publication. The Boolean operators AND and OR were adopted, and inclusion and exclusion criteria were established in the study selection process. From the 155 articles collected in the exploratory search, 9 articles meeting the inclusion criteria were identified, eight case reports and one prospective study. Results and Conclusions: it was found that digital technology, when associated with direct restorations, is an effective tool for both diagnosis and dental treatment. The technique proved to be efficient, as it can be carried out in the dental office itself, providing better communication with the patient, as well as between professionals on the dental team, and the patient will not need to spend a lot of time in the dental office, in addition to promoting better results, aesthetic and functional effects, as well as patient satisfaction.